Subglottic extramedullary plasmacytoma in a patient with multiple myeloma - Martin, Eva M. Ruis de Gauna (2013)
Extramedullary plasmacytoma is a rare tumor, representing approximately 5-10% of all plasma cells neoplasm. The most common location is in head and neck, and the laryngeal involvement is rare with fewer than 100 cases reported. We report the case of a 70 years old patient diagnosed with multiple myeloma in remission, who came to emergency department presenting with progressive dyspnea and stridor, secondary to a cricoid plasmacytoma. One of the problems with cricoid plasmacytomas lies in the difficulty in obtaining a representative histological sample, which may require open biopsy.